FORMULATION AND EVALUATION OF Jasminum sambac Ait. EXTRACT DEODORANT SPRAY PREPARATION WITH A VARIETY OF ALUM - Sholihatil Hidayati; Rikzatus Zahroh; Mohammad Rofiq Usman; Dhina Ayu Susanthi; Diah Yuli Pangesti (LPPM Universitas dr. Soebandi, 2026)
Heavy daily activities often trigger body odor problems, especially in the underarm area, which can reduce comfort and confidence. Body odor arises when Staphylococcus epidermidis breaks down sweat into volatile fatty acid compounds, such as isovaleric acid, which causes an unpleasant odor. This study aims to formulate and evaluate natural deodorant spray preparations containing jasmine flower extract with variations in alum concentration, as well as test the effect of alum variations on the physical quality of preparations. Jasmine flower extract is obtained by maceration method with 70% ethanol for 5 days. Four deodorant spray formulas were prepared with variations in alum concentration (0% as control, 5%, 15%, and 20%). Evaluation of the physical quality of the preparation, including pH, homogeneity, organoleptic, spray pattern, drying time, and effect on fabric, was carried out on days 0, 7, and 14. pH data, spray pattern and dry time were analyzed using One-Way ANOVA and LSD. All formulas show good physical quality, the pH of the preparation meets the pH standard of a good deodorant (3.00-7.5), homogeneous, has a suitable spray pattern (diameter 5-7 cm), a quick drying time (<5 minutes), and does not damage the fabric. Organoleptically speaking, all formulas are liquid in texture and scented with menthol. However, there is a color difference as the concentration of alum increases, the controls are yellowish-orange, F1 is clear yellow, F2 and F3 are solid yellow. Statistical analysis showed that variations in alum concentration had a significant influence on the results of spray patterns (p< 0.05) and drying time (p< 0.05). The physical quality of the deodorant spray, which was tested including pH, homogeneity, organoleptic, spray pattern, drying time and effect on the fabric met the quality standards. However, differences in alum concentrations affect their spray patterns, drying time, and organoleptic, where the concentration of 5% is clear yellow, while 15 and 20% are deep yellow.